COMPARISON OF ACADEMIC ACHIEVEMENT OF MADRASAH STUDENTS AND GENERAL SCHOOLS: EMPIRICAL STUDY OF THE IMPACT OF THE LEARNING ENVIRONMENT IN MADRASHA ON THE EMOTIONAL SOCIAL DEVELOPMENT OF STUDENTS - Supian Ramli; Komari Komari; Taswiyah (Indonesian Journal of Education (INJOE), 2023)
Madrasah and public schools are educational institutions that both provide education to students, but on the other side there are differences. From such differences to display different patterns of academic achievement and social emotional development of students. The methods used in this study are literature by searching for literature that fits the context of the research. Studies have shown that the learning environment in madrasas and schools can influence the development of social and emotional competence of students. Madrasas because they are supported by religious values and ethical norms have been shown to have a positive influence on the ability of students in managing emotions, building healthy relationships, setting goals, and making decisions in their lives. Thus, both institutions should pay attention to the quality of the learning environment and the social environment to ensure that the development of such competences takes place well. One of the things that can be done is to strengthen the social and emotional curriculum in education, to train teachers on appropriate learning approaches to develop students' social and Emotional Skills, and to build an environment that supports the development of such Skills.